EVALUATION OF INFLAMMATORY STATE IN DIABETIC PATIENTS BY MEASURING OF INTERLEUKIN-6 AND TUMOR NECROSIS FACTOR-? IN OBESE AND NON-OBESE TYPE 2 DIABETES MELLITUS PATIENTS AS COMPARED WITH CONTROL SUBJECTS (Iraqi Journal of Medical Sciences, 2017)
Background: Inflammation was one of the most important events in the biology of obesity; the obese subjects were recognized recently as characterized by low-grade chronic inflammation. It was thought that the mild inflammation associated with obesity, and particularly the production of inflammatory adipocytokines like interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-?), was important in the etiology of the diseases associated with obesity. In particular, insulin resistance (IR) and type 2 diabetes mellitus (T2DM).Objective: To investigate whether IL-6 and TNF-? play an important role in the etiology of IR and T2DM.Methods: This study enrolled 70 T2DM patients randomly assigned into two subgroups, 35 non-obese (body mass index (BMI) < 30) diabetic group 1 and 35 obese (BMI ? 30) diabetic group 2 with another 50 healthy control volunteers, divided into two subgroups, 25 non-obese (BMI < 30) control group 1 and 25 obese (BMI ? 30) control group 2. Levels of IL-6, TNF-?, fasting glucose, fasting insulin, HbA1c, homeostasis model assessment of IR (HOMA-IR), homeostasis model assessment of ?-cell function (HOMA-B%) were examined.Results: The serum concentration of IL-6 of obese and non-obese diabetic patients was significantly (p < 0.05) lower as compared with obese and non-obese controls in contrast to the serum concentration of TNF-?, which was significantly (p < 0.05) higher in non-obese diabetic patients in comparison to non-obese controls. No significant correlation was observed for the levels of IL-6 and TNF-? with BMI of study populationConclusion: The proposed link between serum inflammatory cytokines (IL-6 and TNF-?) and T2DM was more related to insulin sensitivity, insulin secretion and/or glycemic control than to adiposity. Therefore, the inflammatory cytokines may play an important role in the etiology of IR and T2DM.Keywords: IL-6, TNF-?, type 2 diabetes mellitus, obesity, insulin resistance.Citation: Qasim QA, Fareed YY, Hassan JK. Evaluation of inflammatory state in diabetic patients by measuring of interleukin-6 and tumor necrosis factor-? in obese and non-obese type 2 diabetes mellitus patients as compared with control subjects. Iraqi JMS. 2017; Vol. 15(3): 297-304. doi: 10.22578/IJMS.15.3.12
Keywords: IL6; TNF; type 2 diabetes mellitus; obesity; insulin resistance